2023
DOI: 10.1038/s41598-023-37216-8
|View full text |Cite
|
Sign up to set email alerts
|

Data mining on identifying diagnosis and prognosis biomarkers in head and neck squamous carcinoma

Abstract: Head and neck squamous carcinoma (HNSC) induces high cancer-related death worldwide. The biomarker screening on diagnosis and prognosis is of great importance. This research is aimed to explore the specific diagnostic and prognostic biomarkers for HNSC through bioinformatics analysis. The mutation and dysregulation data were acquired from UCSC Xena and TCGA databases. The top ten genes with mutation frequency in HNSC were TP53 (66%), TTN (35%), FAT1 (21%), CDKN2A (20%), MUC16 (17%), CSMD3 (16%), PIK3CA (16%), … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…In an earlier study, protein-protein interaction network-based analyses similarly identified ACTN2, MYL1, MYL2 , and MYH7 as hub genes associated with PTEN -associated prostate cancer ( Sun et al 2019 ). The dysregulation of ACTN2 and MYH7 has been described in the context of other cancers ( Ju et al 2023 ). Our results suggest that candidate genes in the identified module can be further examined in the context of prostate cancer.…”
Section: Resultsmentioning
confidence: 99%
“…In an earlier study, protein-protein interaction network-based analyses similarly identified ACTN2, MYL1, MYL2 , and MYH7 as hub genes associated with PTEN -associated prostate cancer ( Sun et al 2019 ). The dysregulation of ACTN2 and MYH7 has been described in the context of other cancers ( Ju et al 2023 ). Our results suggest that candidate genes in the identified module can be further examined in the context of prostate cancer.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, the higher mortality of subtype C1 could indicate a more invasive disease trajectory and greater expression of genes from the MYH family, ACTB, ACTN2, and FLNC. Several studies have reported the prognostic value of the MYH family genes MYL1, MYL2, MYH1, MYH2, and MYH7, which are unfavorable prognostic markers in HNSCC and might promote CD4 + T-cell activation (Li et al 2023 ; Ju et al 2023 ). The level of phosphorylated MYH2-Y1381 is reportedly significantly lower in recurrent HNSCC patients than in primary patients (Kaneko et al 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…[ 30 ] Additionally, lower expression of ACTN2 and MYH1 has been associated with longer OS time in patients with head and neck squamous carcinoma. [ 31 ]…”
Section: Discussionmentioning
confidence: 99%